George V. Boynton papers - Boynton, Henry V. (Henry Van), 1835-1905.
Correspondence, memoranda, reports, and clippings concerning Boynton as President of the District of Columbia Board of Education, and to the investigation of certain school officials in the District's public school system.
Soldier, author, and educator.
Collection material in English.
Keywords: District of Columbia. -- Board of Education; Education -- Washington (D.C.); Educators